The management performance and the absorption of graduation - Khoiriyah Siti, Hendrowati Tri Yuni, (Opción, 2019)
This article analyzes the performance management shown through absorption of graduates into the world of work, satisfaction of HR and HR performance that includes faculty and academic staff. This research is descriptive research with method of documentation. The results showed that more than 87 percent have been absorbed into the world of work that showed MPL has developed a curriculum of high school teacher training and education so well that according to user needs graduates. In conclusion, the Satisfaction of HR indicated that the quantity or quality of something produced or services rendered by a person who does the job.